Pemilihan Komandan Komando Distrik Militer Menggunakan Metode WASPAS - Juniar Hutagalung; Ahmad Fitri Boy; Dicky Nofriansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
At the Military District Command Defense Agency (Kodim) 0201/BS Medan, it requires a Decision Support System (SPK) by applying the web-based Weighted Aggregated Sum Product Assessment (WASPAS) method in the selection process for the Commander of the 0201/BS Medan Kodim. Previously, the selection process was done manually, there were often obstacles in the process of calculating data, assessing, and storing data for each TNI personnel. The process of calculating numbers and data takes quite a long time for the members of the assessment team, so that it has an impact on the selection process that is less than optimal and can affect decision making that must be accurate and fast. The solution to overcome this problem is to create an SPK using the web-based WASPAS method. The purpose of this study is as a recommendation to assist the leadership in selecting the Candidate for the Commander of the Military District Command (Kodim) 0201/BS Medan, quickly even though the data processed is quite large. The calculation results obtained the top 5 alternatives, namely Bina Satria (A7), Azwar (A10), Soni Putrawan Ginting (A3), Agus Miadi (A4), Nirmawan (A2). The ranking after being sorted from the highest Qi value is 0.818261515 under the name of Bina Satria and the lowest Qi value is 0.690876555 under the name of Sabur Utomo